Career Development of State Civil Apparatus at Tomohon’s Personnel and Human Resources Development Agency - Yana Grice Soway; Marthinus Mandagi; Fitri Herawati Mamonto (Syntax Corporation Indonesia, 2022)
This research aims to analyze the implementation of career development of state civil servants at Tomohon's Personnel and Human Resources Development Agency. The focus of this research includes two indicators of competency education qualifications. This research uses qualitative research methods and data collection techniques: Observation, Interview, and Documentation. Primary data of this research are Civil Servants at Tomohon's Personnel and Human Resources Development Agency, and secondary data are documents, archives, and related literature. The results showed that the Civil Service and Human Resources Development Agency of Central Tomohon is generally are preparing for the career development implementation. It can be seen from the performance not going well since there are no regional regulations that technically regulate career development, educational qualifications in structural positions in the placement of educational background are not under the field, or cognate and competency standards in the class have no technical competence. The advice given is career development in Tomohon's Personnel and Human Resources Development Agency. Thus, evaluating employees' placement based on educational background qualifications and field is needed. Regional regulations competency standards in career development are immediately made to map competency standards for employees at Tomohon's Personnel and Human Resources Development Agency.